Exploring the relationship between species richness and intraspecific trait variability. - Dvořáková, Hana (Jihočeská univerzita, 2015)
This thesis was originated as a contribution to the wide range of biodiversity studies published recently. It focused on the little explored importance of intraspecific variability in plant communities. A pot experiment hold in glasshouse environment was designed to observe influence of biotic interactions in mixtures of various species diversity on species functional traits and productivity. Variability of functional traits of individual species was assessed in relation to increasing species richness and the contribution of within-species variance to the total variance of pot communities was evaluated at different richness levels.
Exploring the relationship between species richness and intraspecific trait variability.
Keywords: community ecology; intraspecific variability; species richness; plant traits